The effect of sesamol on endogenous substances and oxidative stability of walnut oil - Cheng, Qin; Bao, Yuanyuan; Lin, Qi; Qi, Tingmei; Zhang, Xinyong (Frontiers in Nutrition, 2024)
This study explored the effect of sesamol on the stability of walnut oil based on the changes of endogenous characteristics in the oxidation process, which provided a theoretical reference for the application of natural antioxidants in walnut oil. A total of 300-mg/kg sesamol (SP), compound antioxidant AC (sesamol 353.62 mg/kg, citric acid 149.60 mg/kg, and BHA 76.33 mg/kg) and 35% sesame oil (35%-SO) were added to walnut oil respectively; in addition, 200-mg/kg t-butylhydroquinone (TBHQ), butylated hydroxyanisole (BHA), and citric acid were used as controls and blank walnut oil to study their effects on peroxide value, acid value, carbonyl compounds, conjugated olefins, phenols, flavonoids, sterols, vitamin E, β-carotene, and 51 fatty acids of walnut oil and their correlation between endogenous antioxidant components. The results showed that the addition of SP, 35%-SO, and AC could inhibit the increase of peroxide value, acid value, and carbonyl compounds in walnut oil, and could inhibit the decrease of β-carotene, total phenols, total sterols, and vitamin E. SP and 35%-SO could inhibit the decrease of total flavonoids, and several antioxidants could inhibit the decrease of endogenous antioxidant components in walnut oil. At the same time, it can better inhibit the change of unsaturated fatty acids in walnut oil. By the end of oxidation, the unsaturated fatty acids of blank walnut oil decreased by 10.31 %, but AC, SP, and 35%-SO treatment groups increased by 10.90%, 5.09% and 4.13%, respectively. indicating that it had a certain protective effect on unsaturated fatty acids in walnut oil. There was a certain correlation between the endogenous substances of walnut oil. so the addition 2 of several antioxidants can enhance the endogenous antioxidants of walnut oil, inhibit the oxidation of unsaturated fatty acids, and inhibit the increase of carbonyl compounds, codienes, acid value, and peroxide value. SP and AC have better antioxidant effects on walnut oil and improve the stability of walnut oil.